FACTORS AFFECTING THE DISCLOSURE OF THE CRIME OF FRAUD, WHICH IS CARRIED OUT TODAY IN THE CITY OF TASHKENT USING INFORMATION TECHNOLOGY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Socio-political processes, trends taking place in the world promote the demand for the further development of liberal democratic principles of national and international relations. Ensuring constructive dialogue between the state and society, the organization and support of national policy, based on the rapid and modern international demands of domestic and foreign policy, are setting new tasks for the political elite. The secret of such tasks requires the conduct of socio-political activities aimed at ensuring the stability of the internal environment, the formation of socio-political consciousness and thinking of members of society, their protection from the harmful effects of the external environment on various manifestations. In the era of globalization and global informatization, the Coordination of these processes is directly related to the organization and conduct of effective information policy. In turn, the effective information policy of the state, in addition to accelerating the solution of existing problems, acquires a specific positive scope in such aspects as ensuring transparency, openness of the activities of state authorities, bringing their dialogue with the people to a new level.